THE IMPACT OF TRANSLATION ON FOREIGN LANGUAGE LEARNING (Web of Discoveries: Journal of Analysis and Inventions, 2025)
The significance of this approach in instructing students is extensively discussed in this article, as is the function that translation plays in learning a foreign language, as well as its efficacy as a method of language acquisition.